Gangguan Neurotik dan Gangguan Stress Pasca Bencana - Muhammad Dicky Firenza; Fazil Amris (Lembaga Pengembangan Kinerja Dosen, 2024)
Disasters are a series of events or occurrences that cause ecological damage, eliminate many lives, cause damage to infrastructure and public facilities and services, and worsen public health or health facility services. The survey showed that, after a disaster event, the results of early detection of anxiety symptoms carried out on disaster victims showed that as many as 85.11% of people experienced anxiety within normal limits, while 14.89% fell into the clinical anxiety category. Around 15-20% of the population will experience mild or moderate mental disorders which refer to Post-Traumatic Stress Disorder (PTSD), while 3-4% will experience severe disorders such as psychosis, severe depression and high anxiety..